CDMetaPOP: an individual‐based, eco‐evolutionary model for spatially explicit simulation of landscape demogenetics. Issue 1 (16th July 2016) - Landguth, Erin L.; Bearlin, Andrew; Day, Casey C.; Dunham, Jason
Summary: Combining landscape demographic and genetics models offers powerful methods for addressing questions for eco‐evolutionary applications. Using two illustrative examples, we present Cost–Distance Meta‐POPulation, a program to simulate changes in neutral and/or selection‐driven genotypes through time as a function of individual‐based movement, complex spatial population dynamics, and multiple and changing landscape drivers. Cost–Distance Meta‐POPulation provides a novel tool for questions in landscape genetics by incorporating population viability analysis, while linking directly to conservation applications.